A aprendizagem do empreendedorismo e a sua influência no processo de criação de empresas - Schneider, Anderson (2016)
The aim of this study was to understand the influence of learning history of nascent entrepreneurship about start-up process and the future performance of the companies. To this end, we used the Panel Study of Entrepreneurial Dynamics II (PSED II) as a sample. This is a panel involving 1214 United States entrepreneurs were accompanied during the years of 2005 to 2011 through telephone interviews on various topics involving the business creation process. The study had as theoretical axis organisational learning and learning entrepreneurship and was developed in two stages, the first being with the specific objective of assessing the causal relationship between learning history of entrepreneurs and the activities of start-up process by which we used the method of multiple linear regression. The second involved the assessment of the causal relationship between the realization of activities of the startup process and the future performance of the companies using logistic regression methods. The results demonstrate that the learning history of entrepreneurs favors the activities of business creation process, and these in turn, when carried out, increase the chances of the businesses achieve best performance results, translated in conducting sales and achieving a balance between revenue and expenditure. It was noted also that the learning history by itself does not have significant relations with the performance.